Banking Governance in Algeria: Reality and Prospects, Empirical Study using an Efficiency Approach - TALHAOUI , Fares; DERRARDJA , Nazim (Journal of Research in Finance and Accounting, 2022)
The purpose of this paper is to assess and to examine the main characteristics of the governance in the Algerian banking system in the framework of the international norms and standards. We use an empirical study based on a non-parametric method called Data Envelopment Analysis (DEA) over a panel of 12 Algerian banks spanning the period 2010-2019.The findings reveal that the governance system of public banks proved a weakness in terms of effectiveness compared to that of private banks. Further, the results of the econometric tests obtained indicate that factors including " The mechanisms relating to the director’s independence, frequency of Board meetings, the separation of control and decision-making functions and the ownership structure " lead to a good governance of the banking system and build effective solutions to improve the performance.